Pattern electroretinograms become abnormal when background diabetic retinopathy deteriorates to a preproliferative stage: possible use as a screening test. Issue 5 (May 1986) - Arden, G B; Hamilton, A M; Wilson-Holt, J; Ryan, S; Yudkin, J S; Kurtz, A
Abstract : The pattern electroretinogram (PERG) and other tests were given to a selected group of patients with diabetes, ranging from those who had no retinopathy or funduscopic changes to those in the preproliferative state. None had visual symptoms. The PERG was found to be normal in patients with microaneurysms and a few blot haemorrhages. However, when cotton-wool spots and angiographic evidence of areas of capillary non-perfusion were present, the PERG was reduced below the normal value. Similar changes occurred with the oscillatory potentials of the ERG evoked by an intense flash, but the results were more variable. So in the individual patient the test is not a reliable indicator of the progress of the retinopathy. The value of the PERG in screening is discussed.